2014
DOI: 10.1590/sajs.2014/20140111
|View full text |Cite
|
Sign up to set email alerts
|

Open access in South Africa: A case study and reflections

Abstract: In this paper, we locate open access in the South African higher education research context where it is, distinctively, not shaped by the policy frameworks that are profoundly changing research dissemination behaviour in other parts of the world. We define open access and account for its rise by two quite different routes. We then present a case study of journal publishing at one South African university to identify existing journal publishing practices in terms of open access. This case provides the springboa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 9 publications
(8 reference statements)
1
26
0
Order By: Relevance
“…11 As the EU moves forward with open access policies, it will be crucial for African countries, especially South Africa, to take a strong stance in support of open access, not only to protect their research interests, but also to maintain the goal of increasing the global sharing of scientific knowledge. 12,13 With these efforts, South Africa may also benefit from tailored open access policies that better meet the needs of their knowledge users and producers. There are two pathways to open access that the EU will rely on: green (self-archiving) and gold (publishing in open access journals).…”
mentioning
confidence: 99%
“…11 As the EU moves forward with open access policies, it will be crucial for African countries, especially South Africa, to take a strong stance in support of open access, not only to protect their research interests, but also to maintain the goal of increasing the global sharing of scientific knowledge. 12,13 With these efforts, South Africa may also benefit from tailored open access policies that better meet the needs of their knowledge users and producers. There are two pathways to open access that the EU will rely on: green (self-archiving) and gold (publishing in open access journals).…”
mentioning
confidence: 99%
“…As previously stated, OA came into existence partly because the price of journals and other publications for institutions has become prohibitively high (Czerniewicz & Goodier, 2014). OA has made volumes of published works free via the Internet (Beall, 2013d).…”
Section: Open Access Publishingmentioning
confidence: 99%
“…Czerniewicz and Goodier (2014) stressed the "research-driven model" (p. 8) should be a continuing conversation among academics and researchers to ensure the quality of the research is not compromised. Despite the potential negative impact from open-access publishing, OA serves a benefit to scholarly communities because it allows a broader set of researchers to contribute their work to the body of knowledge (Czerniewicz & Goodier, 2014;Perry, 2014). Dudley (2013) reported that institutions are the biggest culprit when it comes to predatory publishing.…”
Section: Open Access Publishingmentioning
confidence: 99%
“…Chan et al (2005) and Dulle et al (2013). 55 Chan et al (2005), Czerniewicz and Goodier (2014) and Veldsman and Gevers (2014). machinery, equipment, specialised and trained personnel is unaffordable for most DCs.…”
Section: Open Bioinformation In the Developing World: An Overviewmentioning
confidence: 99%